Simulations of Glomerular Shear and Hoop Stresses in Diabetes, Hypertension, and Reduced Renal Mass using a Network Model of a Rat Glomerulus. Issue 18 (19th September 2020) - Richfield, Owen; Cortez, Ricardo; Navar, L. Gabriel
Abstract: A novel anatomically accurate model of rat glomerular filtration is used to quantify shear stresses on the glomerular capillary endothelium and hoop stresses on the glomerular capillary walls. Plasma, erythrocyte volume, and plasma protein mass are distributed at network nodes using pressure differentials calculated taking into account volume loss to filtration, improving on previous models which only took into account blood apparent viscosity in calculating pressures throughout the network. Filtration is found to be heterogeneously distributed throughout the glomerular capillary network and is determined by concentration of plasma proteins and surface area of the filtering capillary segments. Hoop stress is primarily concentrated near the afferent arteriole, whereas shear stress is concentrated near the efferent arteriole. Using parameters from glomerular micropuncture studies, conditions of diabetes mellitus (DM), 5/6‐Nephrectomy (5/6‐Nx), and Angiotensin II‐induced hypertension (HTN) are simulated and compared to their own internal controls to assess the changes in mechanical stresses. Hoop stress is increased in all three conditions, while shear stress is increased in 5/6‐Nx, decreased in HTN, and maintained at control levels in DM by the hypertrophic response of the glomerular capillaries. The results indicate that these alterations in mechanical stresses and the consequent release of cytokines by or injury of the glomerular cells may play a significant role in the progression of glomerulopathy in these disease conditions. Abstract : We use a novel mathematical model of blood flow and filtration in an anatomically accurate glomerular microvascular network to quantify mechanical stresses and filtration dynamics for each glomerular capillary. Using hemodynamic data from previous literature, we simulate hypertensive, diabetic and renoprival conditions to demonstrate that mechanical stresses are changed due to alterations in pressure and flow in these disease states. Our results indicate that mechanical stress may play a crucial role in the cause and/or progression of glomerular injury in these disease conditions.